(untitled) (Eurasian Journal of Physics,Chemistry and Mathematics, 2022)
In the present paper, pure polymeric blend films [PVA: PVP] reinforced by CaCl2.2H2O salt have been produced with different weight ratios (10,20,30,40,50 wt %) by using the solution casting method. The effect of the weight ratio of the salt upon true density of reinforced polymeric blend films was studied, where the experimental results showed an increase in the true density with increasing weight ratio of added salt. The apparent porosity of reinforced polymeric blend films was determined, and it was found that the apparent porosity decreases as weight ratio of the added salt is increased. The water absorbance of the reinforced polymeric blend films has been investigated as well, and experimental results have revealed that water absorbance decreases with the increase in weight ratio of the added salts